Dacryoadenitis associated with linear scleroderma en coup de sabre: A case report and review of literature - Eva Oustabassidis; Shay Keren; Joel David; Jonathan H. Norris (Wiley, 2024)
Abstract Dacryoadenitis in the setting of linear scleroderma en coup de sabre (LScs) is an association that has not previously been described in the scientific literature. The purpose of this case report is to describe the co‐existence of LScs and chronic dacryoadenitis and how it was managed. We report the case of a 42‐year‐old woman who presented with a 4‐month history of left upper eyelid swelling with radiological enlargement of the left lacrimal gland on orbital CT and MRI imaging. Clinical examination revealed a left erythematous, swollen upper eyelid with lateral conjunctival injection and a palpable left lacrimal gland. An ipsilateral band‐like cutaneous depression in the fronto‐temporal region was also noted, which extended to the ipsilateral upper eyelid and brow. Serology revealed nucleolar antinuclear antibodies. A further incisional biopsy of the lacrimal gland confirmed chronic inflammatory changes and fibrous tissue. Based on both the histological and clinical findings, a diagnosis of dacryoadenitis in association with LScs was made. Oral methotrexate was commenced. The patient responded well with less frequent episodes of eyelid swelling and reduced periocular pain. This case describes for the first time, the ophthalmological manifestation of chronic dacryoadenitis in association with linear scleroderma en coup de sabre.